Entrepreneurship and Innovation in Telemedicine Adoption Among Physicians in Indonesia - Setiawaty, Elika; Hartoyo, Hartoyo; Nurmalina, Rita; Yuliati, Lilik Noor (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study examines the factors driving telemedicine adoption among physicians in Indonesia, employing an integrated framework based on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). The framework investigates the influence of performance expectancy, effort expectancy, facilitating conditions, social support, and economic value on physicians behavioral intention and actual use of telemedicine, with attitude acting as a key mediating variable. Additionally, demographic characteristics, including age, practice type, and practice duration, are explored as potential moderators in these relationships. Data was gathered from a cross-sectional survey of 244 physicians across various specialties and regions in Indonesia. The study findings, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), reveal that effort expectancy, facilitating conditions, social support, and economic value significantly influence both behavioral intention and actual use. In contrast, performance expectancy does not have a significant effect. Attitude plays a crucial mediating role in translating physicians perceptions into adoption behaviors. Moreover, practice type moderates the path from behavioral intention to actual use, with general practitioners more likely to adopt telemedicine than specialists. The results emphasize that telemedicine strategies should prioritize usability, economic value, social support, and institutional backing. This study contributes to the telemedicine adoption literature by extending TAM and UTAUT with attitudinal mediation and economic value, while highlighting emerging psychosocial factors in Southeast Asia. These insights offer practical guidance for healthcare managers and policymakers.